Lead Poisoning - A Global Issue of Great Concern of Modern Times - Shirley Mani, Monica; Joshi, Manjunath B; Kabekkodu, Shama P; D’Souza, Herman S (International Journal of Innovative Research in Medical Science, 2016)
Lead is a non-essential, public health toxin. The entry of this silent poison into the ecosystem has become an issue of great concern at the global level. However, deliberate efforts are undertaken by several governmental and non-governmental organizations to deal with the problem. The ongoing lead poisoning issues can be tackled with ease only through proper countrywide lead awareness campaigns and legislation of strategies and policies in association with lead safety and prevention. By following safe work practices and consumption of healthy diet, the toxic manifestations of lead could be minimized. This review highlights some of the health issues with reference to the current lead exposure status and strategies that can be implemented to assess lead poisoning.